Investigation of Melia Azedarach L. Leaves and Fruits Aqueous Extract Chemical Content - اسماعيل ميس; ياسر موسى; عماد حويجة (Latakia University Journal -Basic Sciences Series, 2022)
Fresh fruits sample abstracted by Clevenger method has showed existence of 58 products as 100% as the follows: 37.66% nitrogen-based compounds, 36.17% hydrocarbons, 21.47% oxygen’s-based compounds and 4,7%of the residual, furthermore, the leaf sample has showed the presence of 34 compounds represented the 99.5% of the percentage as 24.99% oxygen-based , 17.078% hydrocarbons, 13.81% nitrogen-based and 43.62% of the residual.